Alzheimer’s disease marker phospho-tau181 is not elevated in the first year after moderate-severe TBI - Graham,N; Zimmerman,K; Heslegrave,A; Keshavan,A; Moro,F; Abed-Maillard,S; Bernini,A; Dunet,V; Garbero,E; Nattino,G; Chieregato,A; Fainardi,E; et al. (Journal of Neurology, Neurosurgery and Psychiatry, 2024)
Background: Traumatic brain injury (TBI) is associated with the tauopathies Alzheimer’s disease and chronic traumatic encephalopathy. Advanced immunoassays show significant elevations in plasma total tau (t-tau) early post-TBI, but concentrations subsequently normalise rapidly. Tau phosphorylated at serine-181 (p-tau181) is a well-validated Alzheimer’s disease marker that could potentially seed progressive neurodegeneration. We tested whether post-traumatic p-tau181 concentrations are elevated and relate to progressive brain atrophy.Methods: Plasma p-tau181 and other post-traumatic biomarkers, including total-tau (t-tau), neurofilament light (NfL), ubiquitin carboxy-terminal hydrolase L1 (UCH-L1) and glial fibrillary acidic protein (GFAP), were assessed after moderate-to-severe TBI in the BIO-AX-TBI cohort (first sample mean 2.7 days, second sample within 10 days, then 6 weeks, 6 months and 12 months, n=42). Brain atrophy rates were assessed in aligned serial MRI (n=40). Concentrations were compared patients with and without Alzheimer’s disease, with healthy controls.Results: Plasma p-tau181 concentrations were significantly raised in patients with Alzheimer’s disease but not after TBI, where concentrations were non-elevated, and remained stable over one year. P-tau181 after TBI was not predictive of brain atrophy rates in either grey or white matter. In contrast, substantial trauma-associated elevations in t-tau, NfL, GFAP and UCH-L1 were seen, with concentrations of NfL and t-tau predictive of brain atrophy rates.Conclusions: Plasma p-tau181 is not significantly elevated during the first year after moderate-to-severe TBI and levels do not relate to neuroimaging measures of neurodegeneration.